Potential of Physalis angulata fruit extract in improving nutritional status in protein-energy malnutrition: An experimental animal study - Lina Lina; Nora Veri (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Malnutrition remains a major concern in Indonesia, with Aceh Province ranking among the top five provinces for stunting prevalence in 2022 (31.2%). Physalis angulata, known for its antioxidant and nutritional content, has not been extensively studied for its role in improving protein-energy malnutrition (PEM). This study aimed to assess the nutritional effects of a Physalis angulata fruit extract on PEM. A quantitative research method with a true experimental post-test only control group design was used on 25 Wistar strain aged 5-6 weeks with a weight of 100-150 g. PEM was induced through a low-protein diet for 56 days, followed by intervention with Physalis angulata extract at 250, 500, and 1000 mg/kgBW for 30 days. The study was performed at the Physiology Laboratory, Faculty of Medicine, Brawijaya University, from May 25 to October 1, 2024. The results showed no significant effect on body length (p = 0.087) but a significant increase in body weight (p = 0.000). In conclusion, the extract can improve weight gain in PEM, although it does not promote linear growth. Further research with varied doses, longer interventions, and time-series measurements is recommended